New T2 lesions enable an earlier diagnosis of multiple sclerosis in clinically isolated syndromes - Dalton, Catherine M.; Brex, Peter A.; Miszkiel, Katherine A.; Fernando, Kryshani; MacManus, David G.; Plant, Gordon T.; Thompson, Alan J.; Miller, David H. (Annals of neurology, 2003)
In clinically isolated syndromes, the new McDonald criteria for multiple sclerosis diagnosis require new gadolinium‐enhancing lesions for dissemination in time at a 3‐month follow‐up magnetic resonance imaging scan. In a cohort of 56 patients, these criteria were specific (95%) but less sensitive (58%) for clinically definite multiple sclerosis at 3 years. If new T2 lesions were allowed as an alternative for dissemination in time, sensitivity increased (74%) with maintained specificity (92%), enabling an accurate diagnosis of multiple sclerosis in more patients. Ann Neurol 2003;53:673–676